Formal description and automate business process throughout the enterprise using system workflow managment - Марченко, Анна Вікторівна; Милостна, Наталія Олександрівна (Eastern-European Journal of Enterprise Technologies, 2011)
This document considers aspects of workflow management systems for automation of complex distributed business processes, analyze the mechanism of building systems design and workflow management. Proposed a set of software tools to achieve optimum results